Indonesian Political Kleptocracy and Oligarchy: A Critical Review from the Perspective of Islamic Law - Anita Marwing (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
This study discusses corruption in the Indonesian political system from Islamic law, particularly regarding the Kleptocracy and political oligarchy. One of the most basic corruption causes comes from an internal personality factor, human character: greed and wasteful. Additionally, some factors also come from human external factors, namely the perpetrators' coercion, because they are tied to a system. Corruption is carried out by individuals and in cooperation/conspiracy between the bureaucracy, corporations, and political parties. Elites called them Kleptocracy and political oligarchy. This research is descriptive qualitative research with an approach based on legal analysis. This research has found several things. First, corruption in the Indonesian political system can be categorized into acts of Ghulul (treachery), Risywah (Gratification/bribery), Khiyanah (Unfaithful), Sariqah (theft), and Hirabah (Grand Theft/ Robbery). Second. From an Islamic perspective, the strategy to eradicate corruption can be carried out by imposing sanctions, including sanctions in the world's dimensions and the hereafter. This research encourages strengthening the socio-religious system, especially among religious leaders, as a preventive and curative form of handling corruption in the political system in Indonesia.